Moral Universalism and the Structure of Ideology - Benjamin Enke; Ricardo Rodríguez-Padilla; Florian Zimmermann (Center for Economic Studies and ifo Institute (CESifo), 2019)
Throughout the Western world, people's policy preferences are correlated across domains in a strikingly similar fashion. Based on a simple model, we propose that what partly explains the particular internal structure of political ideology is heterogeneity in moral universalism: the extent to which an individual's altruism and trust remain constant as social distance increases. In representative surveys with 15,000 respondents, we measure universalism using structured choice tasks. In the data, heterogeneity in universalism descriptively explains a substantial share of desired government spending levels for welfare, affirmative action, environmental protection, foreign aid, health care, military, border control, and law enforcement. Moreover, the canonical left-right divide on issues such as the military or redistribution reverses depending on whether participants evaluate more or less universalist versions of these policies. These patterns hold in the United States, Australia, Germany, France, and Sweden, but not outside the West. We confirm the idea of higher universalism among the Western political left by estimating the universalism of U.S. regions using large-scale donation data and linking this measure to local vote shares.
Keywords: 330